Production of β-glucosidase from wheat bran and glycerol by Aspergillus niger in stirred tank and rotating fibrous bed bioreactors. Issue 10 (October 2016) - Abdella, Asmaa; Mazeed, Tarek El-Sayed; El-Baz, Ashraf F.; Yang, Shang-Tian
Graphical abstract: Higher β-1, 4-glucosidase production by A. niger grown on wheat bran and glycerol was obtained in a rotating fibrous bed bioreactor (RFBB) because of better morphology control and mass transfer. Highlights: A. niger can produce β-glucosidase (BGL) with wheat bran and glycerol as substrates. BGL production was low in stirred-tank reactor (STR) inoculated with spores. Higher BGL production was obtained in a rotating fibrous bed bioreactor (RFBB). The improved production was due to better fungal morphology and mass transfer. RFBB provides a promising process for economical production of BGL. Abstract: Aspergillus niger NRRL 3112 can produce considerable amounts of β-1, 4-glucosidase (BGL) when grown on wheat bran and glycerol as co-substrates. BGL production was first investigated in a stirred-tank bioreactor (STR) at 450 rpm and 2 vvm. About 5.4 U/mL BGL was obtained using spore suspension as inoculum, whereas a higher production of 9.3 U/mL was obtained using precultured cell pellets. The production of BGL in batch, fed-batch and repeated batch modes in a rotating fibrous bed bioreactor (RFBB) was then studied and compared to the STR. The highest BGL productivity of 1.78 U/mL/day was obtained in the RFBB operated at a repeated batch mode, which was slightly higher than that (1.65 U/mL/day) obtained in the STR with preformed cell pellets and about 1.75-fold of that (1.02 U/mL/day) for the free-cell fermentation in STR inoculated with spores. This work demonstrated that the RFBB could provide an efficient process for β-glucosidase production from low-cost wheat bran and glycerol.